2015
DOI: 10.1136/thoraxjnl-2015-207770.74
|View full text |Cite
|
Sign up to set email alerts
|

S68 A longitudinal study characterising a large adult primary ciliary dyskinesia cohort

Abstract: Adult Primary Ciliary Dyskinesia (PCD) has not been well characterised. Patients have varied radiological severity of disease and lung function impairment and limited data is available regarding prognosis. In this retrospective study we describe and characterise a large adult PCD cohort, and identify determinates of disease progression using longitudinal lung function data.We retrospectively analysed 151 adult patients at a single tertiary centre. Overall mortality was 4.6% over a 7-year median follow-up perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…A total of 11 studies were retrieved from the literature search that concerned prevalence, clinical impact and management of P. aeruginosa infection in patients with PCD [5,6,9,11,[20][21][22][23][24][25][26].…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 11 studies were retrieved from the literature search that concerned prevalence, clinical impact and management of P. aeruginosa infection in patients with PCD [5,6,9,11,[20][21][22][23][24][25][26].…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Three observational studies both showed worse CT scan scores in patients with PCD chronically infected with P. aeruginosa compared to non-infected patients [6,11,20] whereas convincing impact of P. aeruginosa infection on lung function was not consistently found among four included studies [11,23,25] as only one study out of four showed decreased FEV 1 in P. aeruginosa infected patients.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dr Shah reported data from 151 adult patients with primary ciliary dyskinesia at a tertiary referral centre in London. Risk factors for lung function decline in relation to severity of disease on high-resolution CT and ciliary ultrastructure, but interestingly were not associated with Pseudomonas aeruginosa colonisation 27 . P aeruginosa was more common in patients diagnosed late, as was lower lung function, emphasising the importance of picking up the disease early 28…”
Section: Introductionmentioning
confidence: 86%